The Effect of Dragon Fruit Juice Consumption on Hemoglobin Levels in Adolescent Girls at SMPN 4 Kepenuhan, Kepenuhan District, Rokan Hulu Regency Year 2024 - Sri Wahyuni; Eka Yuli Handayani (CV. AFDIFAL MAJU BERKAH, 2025)
Adolescent girls are a vulnerable group to anemia due to menstruation, which leads to monthly blood and iron loss, coupled with insufficient iron intake. In Indonesia, the prevalence of anemia among adolescents remains high despite supplementation programs, yet compliance is low. Therefore, alternative non-pharmacological interventions using local foods such as dragon fruit juice, which is rich in iron, vitamin C, and antioxidants, are needed. This study aimed to determine the effect of dragon fruit juice consumption on hemoglobin levels in adolescent girls at SMPN 4 Kepenuhan, Rokan Hulu Regency. The research employed a quantitative quasi-experimental design (one-group pretest–posttest) with a total sample of 15 adolescent girls selected through purposive sampling. Hemoglobin levels were measured before and after intervention using a hemoglobinometer. Data analysis consisted of descriptive statistics and paired sample t-test to assess differences in mean values before and after treatment. The results showed that the average hemoglobin level increased from 9.9 g/dl before intervention to 14.7 g/dl after intervention. Statistical analysis confirmed a significant difference with p < 0.05, indicating that dragon fruit juice has a positive effect on improving hemoglobin levels. In conclusion, dragon fruit juice consumption can serve as an effective food-based intervention to prevent and reduce anemia among adolescent girls. This finding has practical implications for school-based nutrition programs and community health promotion efforts in Indonesia.